The divergence of /pol/: Mustering memes and the techno-organizational identity during the 2016 United States presidential election - Styrpejko, Michelle (Kansas State University, 2020)
Since its inception in 2003, 4chan has influenced internet culture through various events, movements, and memes. 4chan’s discussion board “politically incorrect,” or /pol/ for short, is especially active. While /pol/ has traditionally been utilized as a board for engaging political issues and events, in recent years, the discourse has shifted to the alt-right. Yet this discourse went largely unnoticed by scholars, discounted as the trolling of an online fringe group. However, during the 2016 election, /pol/ users collectively campaigned for Donald J. Trump using traditional and non-traditional political participation and engagement tactics. Some credit /pol /with turning the tide in favor of the GOP candidate. This leads us to question: what drove /pol/’s political participation and political agency in the 2016 election? This thesis examines the /pol/ board across three pivotal dates to gain a better understanding of /pol/ and their political worldview. By utilizing Burke’s cluster analysis, this thesis examines the discourse on /pol/ on the following three dates: (1) May 3, 2016, the day that Donald Trump becomes the Republican nominee, (2) November 8, 2016, the day of the election, and lastly (3) August 11, 2017, day one of the Charlottesville rallies. Through the examination of word use and associations, cluster criticism allows insight into how these rhetors understand themselves and the way in which they organize their world. Moreover, by illuminating the ideas and arguments of these rhetors, this thesis offers a nuanced picture of /pol/’s political self-identity. I find that while /pol/’s political involvement and movement was initially based on an affinity for their God, Emperor Trump, the evolution of their agenda and realization of political power sans Trump suggests something more. More specifically, my analysis reveals (1) a sense of brotherhood expressed on the board, (2) a shifting relationship with Trump, and finally (3) a more sophisticated set of political actors. Lastly, I consider relevant implications and future directions for scholarship. This thesis indicates the need for more study of online social movements and their benefits and drawbacks, while also calling for political campaigns, anti-hate organizations, and the general populace to pay more attention to /pol/ and similar online groups Moreover, this thesis demonstrates that interpretive scholarship provides a needed complement to other methods of researching online organizing. Ultimately, I conclude that /pol/ is much more than a group of trolls; they are very real and capable political actors that deserve further scrutiny.
Keywords: /pol/; Social movements; Political participation; Online; Political agency